Telaah Konsep Asset Bassed Comunity Development Bagi Pembangunan Pariwisata Berbasis Masyarakat - Amanda, Silva; Darwis, Rudi Saprudin (UI Scholars Hub, 2024)
The tourism sector is one of the sectors that contributes the largest foreign exchange in Indonesia. To develop this, the Ministry of Tourism and Creative Economy continues to encourage the community-based tourism industry, with one of them developing a tourist village program. One way to realize the tourist village program in Indonesia is to use the Asset Based Community Development approach by emphasizing the use of potential assets owned by an area. The purpose of this research is to identify the potential or assets that exist in a village/region that can be developed into a tourist village by emphasizing community participation in the implementation process using the Asset Based Community Development approach. In addition, this program is also expected to improve the community's economy so that it is more prosperous and independent. The approach used in this research is a qualitative approach using concept review techniques to clarify, explore, and analyze key concepts found in the literature review. The author uses library materials as references and references for writing, sourced from scientific articles, books, and electronic newspapers that are considered relevant to the topic being studied. The results stated that five main capital/assets can be used in the tourism village development program, namely human, social, physical, financial, and environmental capital. In tourism village development activities, the community must first know what local assets or strengths are owned by the village and then can be developed to support the success of the program, such as the management of natural assets/environment, community, and local culture.